Fine Particle Adsorption Capacity of Volcanic Soil from Southern Kyushu, Japan - Naoaki Misawa; Kentaro Yasui; Kentaro Sakai; Taichi Kobayashi; Hideki Nagahama; Tomohiro Haraguchi; Satomi Sasaki; Vetchapitak Torrung; Taradon Luangtongkum; Takako Taniguchi; Kentaro Yamada; Makoto Minamimagari; et al. (Nanomaterials, 2023)
“Akahoya” is a volcanic soil classified as a special soil deposited in Kyushu, Japan. Many of its properties are not yet clearly understood. We found that Akahoya had the potential to adsorb bacteria in cattle feces, which prompted us to investigate its material properties and perform experiments to comprehensively evaluate its adsorption performance for various fine particles such as acidic and basic dyes, NOx/SOx gas, and phosphoric acid ions, in addition to bacteria. Akahoya had a very high specific surface area owing to the large number of nanometer-sized pores in its structure; it exhibited a high adsorption capacity for both NO2 and SO2. Regarding the zeta potential of Akahoya, the point of zero charge was approximately pH 7.0. The surface potential had a significant effect on the adsorption of acidic and basic dyes. Akahoya had a very high cation exchange capacity when the sample surface was negatively charged and a high anion exchange capacity when the sample surface was positively charged. Akahoya also exhibited a relatively high adsorption capacity for phosphoric acid because of its high level of Al2O3, and the immersion liquid had a very high Al ion concentration. Finally, filtration tests were performed on Escherichia coli suspension using a column filled with Akahoya or another volcanic soil sample. The results confirmed that the Escherichia coli adhered on the Akahoya sample. The results of the Escherichia coli release test, after the filtration test, suggested that this adhesion to Akahoya could be phosphorus-mediated.